Complete mitochondrial genome of the striped scat Selenotoca multifasciata (Perciformes: Scatophagidae). (3rd July 2016) - Liu, Zhenhao; Mu, Xingjiang; Li, Hong; Gui, Lang; Zeng, Wengang; Zhang, Junbin
Abstract: The striped scat Selenotoca multifasciata is an ornamental and commercial fish in Asia . In the present study, we sequenced and annotated the complete mitochondrial genome of Selenotoca multifasciata . Its total length is 16, 646 bp, and the mitochondrial genome is composed of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a non-coding control region. ND6 and eight tRNA genes were encoded on the light strand, whereas the remaining genes located on the heavy strand (H-strand). All the 16 mitochondrial genomes of the suborder Acanthuroidei available in GenBank were employed for phylogenetic analysis, and the result showed a close relationship between Selenotoca multifasciata and Scatophagus argus . This mitochondrial information may benefit relative ecological and phylogenetic studies.